Strategi Pengembangan dan Pemasaran Saham Syariah di Pasar Modal Berbasis Teknologi Digital - Dini Selasi; Adine Ardiyanti; Siti Khoiriyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The sharia capital market has become an important component in supporting sharia-based economic growth. With the rapid development of digital technology, implementing innovative strategies is the key to expanding reach and increasing efficiency in developing and marketing sharia shares. This research aims to identify and formulate effective strategies in developing and marketing sharia shares in digital technology-based capital markets. The research method used is a literature study, which analyzes various literature and secondary data regarding current practices in the Islamic capital market and the adoption of digital technology in this sector. The research results show that the adoption of digital technology, such as online trading platforms and artificial intelligence (AI)-based data analysis, plays a significant role in increasing investor participation, transparency and operational efficiency of the Islamic capital market. In addition, strategies that focus on investor education, innovation in investment products that comply with sharia principles, and collaboration between stakeholders are proven to support the optimization of sharia stock marketing. The implementation of digital technology in sharia stock marketing can increase the attractiveness of sharia-based investments and expand the market. This research is expected to provide strategic insight for regulators, market players and other stakeholders in optimizing the role of digital technology to strengthen the Islamic capital market in a sustainable manner